2021
DOI: 10.3389/ijph.2021.1603975
|View full text |Cite
|
Sign up to set email alerts
|

One Year of the COVID‐19 Pandemic. What Do We Know and What Is Yet to Come? — The Summarising Review

Abstract: Objectives: The aim of this review is to summarize the most relevant scientific discoveries regarding SARS- CoV-2 virus infection, with the special emphasis put on its pathophysiology and way of treatment.Methods: In November 2020, the research articles have been collected and examined manually to pick the most relevant. In case of fresh topics, e.g. vaccines, we have performed searching using adequate keywords. Preliminary analysis was conducted on 200 manuscripts.Results: Among them 59 papers were out-of-sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that cytokine production as part of the immune response, whether from vaccination ( 24 , 25 ) or infection ( 26 ), may transiently interfere with the HPO axis and thus the production of ovarian hormones that drive the menstrual cycle ( 17 , 18 ). To explore the possibility that vaccine-associated menstrual delays observed in the prospective cohort were mediated in this way, we examined the effect of hormonal contraception and timing of vaccination within the cycle on participants' reports: if vaccine effects on menstrual timing are mediated by ovarian hormones, we might expect that supplying these exogenously, as in hormonal contraception, would protect against experiencing changes in cycle length.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cytokine production as part of the immune response, whether from vaccination ( 24 , 25 ) or infection ( 26 ), may transiently interfere with the HPO axis and thus the production of ovarian hormones that drive the menstrual cycle ( 17 , 18 ). To explore the possibility that vaccine-associated menstrual delays observed in the prospective cohort were mediated in this way, we examined the effect of hormonal contraception and timing of vaccination within the cycle on participants' reports: if vaccine effects on menstrual timing are mediated by ovarian hormones, we might expect that supplying these exogenously, as in hormonal contraception, would protect against experiencing changes in cycle length.…”
Section: Discussionmentioning
confidence: 99%
“…At the outbreak of the war, only 37% of citizens were vaccinated against COVID-19, and the booster dose was received by 1.7% of those eligible [18]. Large numbers of unvaccinated individuals may transmit the virus more easily than vaccinated individuals, and given that some SARS-CoV-2 infections are asymptomatic, they may unknowingly infect more people [20]. In the face of the migration crisis, this also translates into a higher chance of outbreaks among refugees, but also an increase in the number of cases among citizens of the countries to which the refugees have arrived.…”
Section: Attitudes Toward Vaccination Against Covid-19 In Ukrainementioning
confidence: 99%